Detection Of Routing Misbehavior In Manet By Enhanced 2ack Scheme Using Dsr Protocol (International Journal of Engineering and Computer Science, 2013)
This paper focuses on routing misbehavior in MANET and method for detection of links which causes misbehavior. In MANET all the interested nodes to participate in routing should be fully co operative. But some nodes refuse to share the resources but get benefits for other nodes. Due to the node mobility, open structure and dynamic topology changes performance of network gets affected. The 2ACK scheme is used to detect such behavior by sending acknowledgement through opposite direction of the routing path. The proposed enhanced scheme using DSR protocol reduces the overhead of acknowledgement by 2ACK scheme